Selective Activation of CNS and Reference PPARGC1A Promoters Is Associated with Distinct Gene Programs Relevant for Neurodegenerative Diseases - Kwik, Markus; Hainzl, Stefan; Oppelt, Jan; Tichy, Boris; Koller, Ulrich; Bernardinelli, Emanuele; Steiner, Markus; Zara, Greta; Nofziger, Charity; Weis, Serge; Paulmichl, Markus; Dossena, Silvia; et al. (International journal of molecular sciences, 2021)
The transcriptional regulator peroxisome proliferator activated receptor gamma coactivator 1A (PGC-1α), encoded by PPARGC1A, has been linked to neurodegenerative diseases. Recently discovered CNS-specific PPARGC1A transcripts are initiated far upstream of the reference promoter, spliced to exon 2 of the reference gene, and are more abundant than reference gene transcripts in post-mortem human brain samples. The proteins translated from the CNS and reference transcripts differ only at their N-terminal regions. To dissect functional differences between CNS-specific isoforms and reference proteins, we used clustered regularly interspaced short palindromic repeats transcriptional activation (CRISPRa) for selective endogenous activation of the CNS or the reference promoters in SH-SY5Y cells. Expression and/or exon usage of the targets was ascertained by RNA sequencing. Compared to controls, more differentially expressed genes were observed after activation of the CNS than the reference gene promoter, while the magnitude of alternative exon usage was comparable between activation of the two promoters. Promoter-selective associations were observed with canonical signaling pathways, mitochondrial and nervous system functions and neurological diseases. The distinct N-terminal as well as the shared downstream regions of PGC-1α isoforms affect the exon usage of numerous genes. Furthermore, associations of risk genes of amyotrophic lateral sclerosis and Parkinson's disease were noted with differentially expressed genes resulting from the activation of the CNS and reference gene promoter, respectively. Thus, CNS-specific isoforms markedly amplify the biological functions of PPARGC1A and CNS-specific isoforms and reference proteins have common, complementary and selective functions relevant for neurodegenerative diseases.
Keywords: Protein Isoforms; Neurons; Transcriptional Activation; nádorové buněčné linie; RNA sequencing; HEK293 Cells; transkriptom; PPARGC1A; Promoter Regions, Genetic; CRISPR; Exons; Cell Line, Tumor; genové regulační sítě; Transcriptome; Gene Regulatory Networks; exon usage; PGC-1α; Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-alpha; HEK293 buňky; protein - isoformy; Humans; aktivace transkripce; neurony; nukleotidové motivy; RNA expression; promotorové oblasti (genetika); neurodegenerativní nemoci; Nucleotide Motifs; CNS-specific transcripts and isoforms; neurodegenerative diseases; exony; Neurodegenerative Diseases; lidé